Problems of Policy Gap in Less Mitigation of Facing Covid-19: Lesson from Bangkalan Regency - Disyacitta, Fikri; Prakasita, Ajeng Widya (UIN Sunan Ampel Surabaya, 2022)
This article aims to identify the weak mitigation policy in response to the increasing case number of Covid-19 and elaborate why lack a sense of crisis among community in Bangkalan Regency occurred. The local government is trying to suppress the increasing number of Covid-19 in Bangkalan Regency by restricting mobility during Eid al-Fitr and cooperating with the Surabaya City government and East Java province authority to provide proper healthcare system. As Bangkalan regency failed to deal with the crisis, Surabaya city government respond the emergency situation with social restriction policy in Suramadu bridge, which ended with rejection from Madurese community. This study uses the interpretive approach and narrative analysis techniques. The article fully uses secondary data from credible mass media and official documents related to handling Covid-19 in Bangkalan Regency from April-June 2021. The concept of policy gap is used as an instrument to analyze the factors that caused the policy failure in the Bangkalan Regency Government of the Covid-19 mitigation in the community. Result shows that not only political policy gap which making both policies ineffective, but also cultural policy gap.